Erratum: Self-assembly of ordered graphene nanodot arrays. Issue 1 (December 2017) - Camilli, Luca; Jørgensen, Jakob; Tersoff, Jerry; Stoot, Adam; Balog, Richard; Cassidy, Andrew; Sadowski, Jerzy; Bøggild, Peter; Hornekær, Liv
Change History: A correction to this article has been published and is linked from the HTML version of this article.